Pollution Caused by Potentially Toxic Elements Present in Road Dust from Industrial Areas in Korea - Hyeryeong Jeong; Jin Young Choi; Jaesoo Lim; Kongtae Ra (Atmosphere, 2020)
We examined the pollution characteristics of potentially toxic elements (PTEs) in road dust (RD) from nine industrial areas in South Korea to assess PTE pollution levels and their environmental risks for devising better strategies for managing RD. The median concentrations (mg/kg) were in the order Zn (1407) > Cr (380) > Cu (276) > Pb (260) > Ni (112) > As (15) > Cd (2) > Hg (0.1). The concentration of PTEs was the highest at the Onsan Industrial Complex, where many smelting facilities are located. Our results show that Onsan, Noksan, Changwon, Ulsan, Pohang, and Shihwa industrial areas are heavily polluted with Cu, Zn, Cd, and Pb. The presence of these toxic elements in RD from the impervious layer in industrial areas may have a moderate to severe effect on the health of the biota present in these areas. The potential ecological risk index (<semantics><msubsup>Eri</msubsup></semantics>) for PTEs was in the decreasing order of Cd > Pb > Hg > Cu > As > Zn > Ni > Cr, indicating that the dominant PTE causing ecological hazards is Cd owing to its high toxicity. Our research suggests the necessity for the urgent introduction of an efficient management strategy to reduce RD, which adds to coastal pollution and affects human health.